Foreign direct investment in China - Dang, Xiaobao (Kansas State University, 2008)
China’s absorbing foreign direct investment (FDI) has contributed importantly to its economy growth. Based on the findings of some previous studies in the literature, this report presents a general review of FDI in China, which includes characteristic, history and regional distribution. In the report, I discuss various economic determinants of FDI (such as market size, labor cost, infrastructure, and government policies) and investigate the impact of FDI on China's economic growth. Furthermore, I discuss challenges, new trends and the future opportunities facing China.
Keywords: Foreign direct investment; China; Economics, Commerce - Business (0505)